PENGARUH PRICE EARNING RATIO, DEBT TO EQUITY RATIO DAN RETURN ON EQUITY TERHADAP HARGA SAHAM PT. MANDOM INDONESIA, Tbk - Aniyah Amalia Saputri; Herry Winarto (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2019)
This type of research uses quantitative research. The data sources used in the study are secondary data. The data analysis method used is hypothesis testing namely f test and t test. The results of this study indicate that Price Earning Ratio, Debt To Equity Ratio, Return On Equity simultaneously have a significant effect on stock prices. Partially Price Earning Ratio, and Return On Equity do not have a significant effect, while Debt To Equity Ratio partially has a significant effect on the stock price of PT Mandom Indonesia Tbk. To get the data, researchers used the website of PT Mandom Indonesia Tbk, and the Indonesia Stock Exchange (IDX). By conducting financial data research during the 2013-2017 period which was analyzed using SPSS 24.0